Entropy framework of the bioconvective Williamson nanofluid flow over a Riga plate with radiation, triple stratification and swimming microorganisms - K. Loganathan; N. Thamaraikannan; S. Eswaramoorthi; Reema Jain (International Journal of Thermofluids)
Nanofluids are crucial in thermal engineering, industrial processes, and biomedical innovations, facilitating improved heat transmission, cooling systems, thermal extrusion techniques, and applications in cancer therapy, especially for brain tumours. Owing to this a comprehensive description of the mixed convective flow of Williamson nanofluid as it flows over a Riga plate with entropy production and motile microorganisms. Are examined. The flow pattern model takes into account the influences of thermal radiation, Cattaneo-Christov heat and mass fluxes, stratifications, thermophoresis, and Brownian motion. Utilizing a suitable conversion approach, translate the partial differential equation (PDEs) system into ordinary differential equations (ODEs). The translated equations are computed analytically by adopting the homotopy analysis method (HAM). Finally, this analysis provides a complete numerical and diagrammatic analysis of the physical factors influencing velocity, temperature, concentration, microorganism fields, skin friction coefficient, Nusselt number, Sherwood number, and microorganism density. It is evident that the thermal stratification parameter dropped the velocity and temperature profiles. The concentration profile is boosted by raising the size of the thermophoresis parameter, while it is diminished by the augmenting values of the Brownian motion parameter. The abundance of microbes is diminished by higher degrees of bioconvection Lewis number and microorganisam stratification parameter. The heat transfer rate is augmented when enriching the values of thermal relaxation parameter.